„Kocham cię, życie”. O darze łgania i opowiadania oraz o budowaniu własnego wizerunku w pamiętnikach Artura Rubinsteina - Cuber, Marta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
In comparison to other classical music players (such as Fiodor Szalapin’s Memories from my life), Arthur Rubinstein’s My early years seem to be a work of a thriller-like fabular layer and an elementary non-fiction value. In my sketch, instead of evaluating this proportion, I suggest making a more useful move — a rhetorical analysis of the auto-creatrional pose which is adopted by the memoir’s subject. By means of this I present the memoir I (which easily embodies roles such as a liar, joker, raconteur and sage), as well as point and decipher the mechanisms of popular prose, which the author activates. Thanks to this approach Rubinstein uncovers his unknown face — a conscious writer and amusement culture hothead. Uncovering its codes in My early years with the evolutionary biography construction of the main character basically means retelling the musician’s diary — this time as well composed, popular literature. By means of this procedure the author’s mistakes and slips of memory become softened, for playing with the reader to persuade him to believe in the maker’s unfailing memory seems to be more important. A separate matter in this sketch is the reflection on the anecdotal-narcisistic layer of the memoir. To open it I use not the rhetorical key, but psychotherapeutic tools, revealing a considerable amount of autotherapy potential in Rubinstein’s memories. Thus, this sketch discloses and exposes the mystifying mechanisms in the work of the great pianist, leveling them with the consoling inclinations of popular biographies.